Dilation of the cystic duct confluence in laparoscopic common bile duct exploration and stone extraction in patients with secondary choledocholithiasis - Yang, Xiao-Bin (BMC Surg, 2020)
BACKGROUND: Many options exist for the management of cholelithiasis and secondary choledocholithiasis. Among them, laparoscopic common bile duct exploration (LCBDE) with choledocotomy followed by laparoscopic cholecystectomy has gained popularity. However, efforts should be made to ensure minimally invasive or noninvasive management of the common bile duct (CBD). The purpose of this study was to explore the clinical experience of non-invasive surgical modality, i.e., laparoscopic transcystic dilation of the cystic duct confluence in CBD exploration (LTD-CBDE), including feasibility, safety, adverse events, and incidence. METHODS: In this retrospective analysis, 68 patients were offered the LTD-CBDE technique from December 2015 to April 2018 based on patient’s own intention. During the surgery, the cystic duct confluence was dilated with separation forceps and/or a columnar dilation balloon. Subsequently, CBD exploration and stone extraction were performed with a choledochoscope. The entrance of the CBD was covered with a cystic duct stump wall and was subjected to primary closure at the end of surgery. RESULTS: Forty-nine females and 19 males with cholelithiasis and secondary choledocholithiasis were included. The mean age was 53 years old (18 to 72 year). Of these patients, 62 (91.2%) were successfully treated with the LTD-CBDE technique, and bile leakage was observed in 3 patients (4.4%). The mean operation time was 106 min, and the mean hospital stay was 5.9 days. Among the other 6 patients, 3 were converted to open cholecystectomy due to severe fibrosis, unclear anatomical structure at Calot’s triangle (n = 2) or Mirizze syndrome (n = 1); LCBDE was performed in 3 patients due to cystic duct atresia (n = 2) and low level of flow from the gallbladder duct into the CBD (n = 1). These patients had a smooth postoperative course. In total, 43/68 of the patients presented no radiological evidence of retained CBD stones at the postoperative follow-up (40 patients treated with LTD-CBDE) 1 year later. CONCLUSIONS: The current work suggests that LTD-CBDE for the management of cholelithiasis and secondary choledocholithiasis is a feasible, safe and effective technique with a low complication rate. LTD-CBDE offers another alternative for surgeons to treat patients in similar scenarios. However, additional randomized, controlled studies are needed to demonstrate its efficacy, safety, and impact on CBD stenosis.